STATISTICS AND MATHEMATICAL ANALYSIS OF THE ROLE OF RESEARCH IN CREATIVITY AND INNOVATION FOR ECONOMIC GROWTH OF BUSINESS SECTOR (Singaporean Journal of Business Economics and Management, 2020)
The Aim of the present paper is to explain in detail the concepts of creativity and innovation from the point of view of the economic growth of Business Sector. The purpose is to highlight the design thinking process as related to the leadership of the organization. The concept of corporate innovation has been discussed at length. Also, the significance of creativity at workplace has been highlighted. The methodology is based on the (i) Mathematical Modeling and optimization of Creativity and Innovation in terms of the expressions for Creativity, Innovation, and Research; and (ii) the Findings of the Researchers given in literature; and finally to suggest an Empirical and Statistical relationship between the two. The implications of the paper should be useful for the Leaders in Business Sector and the Researchers in this field, and encourage them to follow and observe the related norms at the work place by motivating the employees to understand the significance and importance of Creativity and innovation, and then following it's objectives very sincerely in their efforts for improving the economic growth of their Business concern. The other important implication and impact of this paper is to motivate the Business managers to have well designed Departments for constantly observing the growth as a function of these Parameters for taking appropriate corrective steps for it.